EVALUATION STUDY OF THE REALITY OF PUBLIC SPACES IN RESIDENTIAL NEIGHBORHOODS, THE CASE OF THE LAKHDAR AL-SABAA NEIGHBORHOOD IN AL-IDRISSIYA- DJELFA-ALGERIA - Atmani ABDERRAHMAN; Kadri DERRADJI; Othmani OTHMANE (Analele Universităţii din Oradea: Seria Geografie)
Public spaces are the basic element within residential neighborhoods, by their effective role as they are considered a complement to the dwelling space for users, but it suffers from various problems, as it records a state of deterioration that often reflects a lack of design efficiency with the absence of management features for the actors of this component within the residential neighborhoods. In order to determine the totality of this problems, we conducted an evaluation study of the reality of public spaces in residential neighborhoods by choosing the Akhdar Al-Sabaa neighborhood in Al-Idrissiya, where we studied the extent of efficiency and effectiveness and evaluated the participatory performance of residents within the neighborhood through field analysis and comparing the planning of public spaces within the neighborhood with international indicators in the quality of public spaces. Through this research paper, after reading, comparing, and reviewing, we were able to come up with a number of results and solutions in dealing with public spaces and contributing to raising their quality.